Monitoring Individual Sleep and Nocturnal Heart Rate Variability Indices: The Impact of Training and Match Schedule and Load in High-Level Female Soccer Players - Costa, Júlio A.; Figueiredo, Pedro; Nakamura, Fábio Y.; Rebelo, António; Brito, João (Frontiers in Physiology, 2021)
Purpose: To describe individual sleep habits and nocturnal heart rate variability (HRV) responses, and to explore intra-individual associations of workload with sleep and nocturnal HRV indices in high-level female soccer players throughout a 2-week competitive period. Materials and methods: The study followed a descriptive, observational design. Thirty-four high-level female soccer players (aged 20.6±2.3 years) wore wrist actigraph units and heart rate (HR) monitors during night-sleep to record objective sleep and HRV data throughout 14 days (6 evening-time training sessions [ET], 6 rest-days [RD] and 2 match-days [MD]). During each ET and MD, exercise HR (HRexe), %HRpeak, training impulse (TRIMP), session rating of perceived exertion (s-RPE) and perceived ratings of wellbeing were monitored. Results: After ET, a higher number of players (17 to 22) slept less than 7h/night, in contrast to the remaining days (i.e., MD and RD), but only 1 to 6 players had a sleep efficiency <75%. The coefficient of variation (CV) for sleep duration and sleep efficiency ranged between 9 to 22% and 2 to 11%, respectively. A small negative within-subject correlation was found between TRIMP and sleep duration [r = -0.25 (-0.36; -0.12); P<0.001] and sleep efficiency [r = -0.20 (-0.32; -0.08); P=0.004]. A moderate and small negative within-subject correlation was found between s-RPE and sleep duration [r = -0.43 (-0.53; -0.32); P<0.001] and sleep efficiency [r = -0.17 (-0.30; -0.05); P=0.02]. Nocturnal HRV for the time-domain analyses ranged from 4.1 (3.9; 4.3) to 4.4 (4.1; 4.6) ln[ms], and for the frequency-domain analyses ranged from 6.3 (5.9; 6.7) to 7.5 (7.1; 7.9) ln[ms2]. CV for time-domain HRV ranged from 3 to 23%, and from 4 to 46 % for the frequency-domain. Higher CV fluctuations in time- and frequency-domain HRV were particularly observed in 4 players. Conclusion: Overall, this study highlights the individual variability of sleep and nocturnal HRV indices, indicating that sleep duration may be affected by training and match schedules and workloads. Training and matches workload were not associated with nocturnal HRV in high-level female soccer players.